5‐Oxyacetic Acid Modification Destabilizes Double Helical Stem Structures and Favors Anionic Watson–Crick like cmo(5)U‐G Base Pairs - Strebitzer, Elisabeth (Chemistry, 2018)
Watson–Crick like G‐U mismatches with tautomeric G(enol) or U(enol) bases can evade fidelity checkpoints and thereby contribute to translational errors. The 5‐oxyacetic acid uridine (cmo(5)U) modification is a base modification at the wobble position on tRNAs and is presumed to expand the decoding capability of tRNA at this position by forming Watson–Crick like cmo(5)U(enol)‐G mismatches. A detailed investigation on the influence of the cmo(5)U modification on structural and dynamic features of RNA was carried out by using solution NMR spectroscopy and UV melting curve analysis. The introduction of a stable isotope labeled variant of the cmo(5)U modifier allowed the application of relaxation dispersion NMR to probe the potentially formed Watson–Crick like cmo(5)U(enol)‐G base pair. Surprisingly, we find that at neutral pH, the modification promotes transient formation of anionic Watson–Crick like cmo(5)U(−)‐G, and not enolic base pairs. Our results suggest that recoding is mediated by an anionic Watson–Crick like species, as well as bring an interesting aspect of naturally occurring RNA modifications into focus—the fine tuning of nucleobase properties leading to modulation of the RNA structural landscape by adoption of alternative base pairing patterns.